Informed Trading and Intertemporal Substitution - XIAO, YIZHOU (Journal of Finance, 2020)
ABSTRACT I examine the possibility of information‐based trading in a multiperiod consumption setting. I develop a necessary and sufficient condition for trade to occur. Intertemporal substitution introduces a desire to correlate current consumption with future aggregate shocks. When agents have heterogeneous time‐inseparable preferences, information differentially affects relative preferences for current and future consumption, making information‐based trading mutually acceptable. The no‐trade result continues to hold if there is no aggregate shock, or if agents have either homogeneous or time‐separable preferences.